APLIKASI MONITORING CAPAIAN KOMPETENSI PESERTA DIDIK DI SMA KOLOMBO YOGYAKARTA - Saputra, Andika Bayu; Cahyono, Ari (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2018)
Colombo High School is an educational institution in charge of handling activities related to education. As an educational institution at present the 2013 curriculum report data management still uses Microsoft Excel applications with the step of the subject teacher submitting the file value to the homeroom teacher and the homeroom teacher will process the value data and submit it to the curriculum section for printing. Of course this requires a long time and is not effective. Another problem that arises is that the current process is perceived to be less optimal and efficient, the guardian of the student must go to the school every semester which requires a lot of time for the guardians of students who cannot attend the division of the Colombo High School students achievement report and the report can only be seen at a certain time. This research was designed and built using the CodeIgniter framework and uses a MySQL database as well as the System Development Life Cycle (SDLC) method of the waterfall model which can help the school, namely teachers, homerooms and curriculum parts in terms of report card management and for learners.